Estimation of body weight from foot outline length measurements in Melanau population of east Malaysia - T. Nataraja Moorthy,; Hairunnisa Mohd Anas Khan, (Malaysian Society of Applied Biology, 2016)
Forensic resources use footprint analysis to obtain vital information during specific crime scene investigations. The examination of bare foot impression is important especially in Asian countries like India and Malaysia where some of the rural population still walk barefooted. Literature review shows that countable research work was conducted to estimate body weight from foot outline anthropometry. The researchers cautioned that racial and cultural aspects of foot morphology must be considered while conducting the foot print study. Hence the present study aims to derive population specific equations to estimate body weight from foot outline anthropometry from 200 (100 males, 100 females) consented adult Melanau ethnics of east Malaysia. The collected data were analysed with PASW 20 computer software. There is a positive correlation exists between body weight and foot outline length measurements. Correlation coefficient (R) values are found to be higher in the pooled sample (0.257–0.286) when compared with males (0.158–0.264) and females (0.179–0.247). The regression formulae derived from the pooled sample can be used to estimate body weight from foot outline when the sex of the foot outline remains unknown, as in real crime scenarios.